2020
DOI: 10.1038/s41598-020-64626-9
|View full text |Cite
|
Sign up to set email alerts
|

Lacosamide intake during pregnancy increases the incidence of foetal malformations and symptoms associated with schizophrenia in the offspring of mice

Abstract: The use of first and second generation antiepileptic drugs during pregnancy doubles the risk of major congenital malformations and other teratogenic defects. Lacosamide (LCM) is a third-generation antiepileptic drug that interacts with collapsing response mediator protein 2, a protein that has been associated with neurodevelopmental diseases like schizophrenia. The aim of this study was to test the potential teratogenic effects of LCM on developing embryos and its effects on behavioural/histological alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“… 102 , 103 Data from preclinical studies found a high incidence of embryonic lethality and malformations. 104 In mice, morphological alterations in the prefrontal cortex, hippocampus, and amygdala were associated with behaviors associated with schizophrenia spectrum disorders. 104 The number of human lacosamide–exposed fetuses is very low (1–10) but without MCMs.…”
Section: Management Of Epilepsy During Pregnancy and Anti-seizure Med...mentioning
confidence: 99%
See 1 more Smart Citation
“… 102 , 103 Data from preclinical studies found a high incidence of embryonic lethality and malformations. 104 In mice, morphological alterations in the prefrontal cortex, hippocampus, and amygdala were associated with behaviors associated with schizophrenia spectrum disorders. 104 The number of human lacosamide–exposed fetuses is very low (1–10) but without MCMs.…”
Section: Management Of Epilepsy During Pregnancy and Anti-seizure Med...mentioning
confidence: 99%
“… 104 In mice, morphological alterations in the prefrontal cortex, hippocampus, and amygdala were associated with behaviors associated with schizophrenia spectrum disorders. 104 The number of human lacosamide–exposed fetuses is very low (1–10) but without MCMs. 92 , 105 More recent data from NAAPR quote no MCM risk (0.0%, 95% CI = 0.28–13.6).…”
Section: Management Of Epilepsy During Pregnancy and Anti-seizure Med...mentioning
confidence: 99%
“…Despite the development of new ASM, investigations of third generation ASM can generate nervous system malformations in vitro. LCM and its metabolites may have teratogenic effects on the developing mice embryos, reflected in embryonic lethality and malformations, as well as behavioral and histological alterations (López-escobar et al, 2020). Then, LCM generates growth retardation and major malformations increased in a dose-dependent manner and observed mostly in the supratherapeutic group (Mete et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Новонароджені миші, народжені від самок, які отримували лакосамід під час вагітності, демонстрували чітку психомоторну затримку і поведінкові й морфологічні зміни в префронтальній корі, гіпокампі й мигдалині, які пов'язані з поведінковими розладами шизофренічного спектра в дорослому віці. Авторами зроблено висновок, що лакосамід і його метаболіти можуть мати тератогенний вплив на ембріони, що проявляється в ембріональній летальності та вадах розвитку, а також у поведінкових і гістологічних змінах у дорослих мишей, які нагадують ті, що спостерігаються в пацієнтів з шизофренією [34]. Відповідно до рекомендацій FDA у США при вагітності не призначається [35].…”
Section: клінічні особливості лікування фокальної резистентної епілепсіїunclassified